Smoking and Lower Urinary Tract Symptoms - Bolat, Mustafa Suat; Akdeniz, Ekrem; Ozkaya, Sevket; Batur, Ali Furkan; Kutman, Kerem Gencer; Goren, Resit; Erdemir, Fikret; Ece, Ferah (Urology Journal, 2015)
Purpose: Pharmacologic effects of nicotine are multifaceted and complicated. Despite numerous studies, the effect of smoking on lower urinary tract functions, have not been yet studied in detail. In this study, we aimed to investigate the effects of smoking addiction on lower urinary tract and sexual functions on the basis of respiratory functions. Materials and Methods: A total of 186 male patients who have been evaluated between May 2014 and January 2015 were recruited in this study. Smoking history, respiratory symptoms, respiratory function tests, uroflowmetry parameters relating to lower urinary tract symptoms (LUTS), prostate volume, post-voiding residual urine volume and sexual functions of patients have been retrospectively investigated. Results: We determined that as the mean number of cigarettes smoked daily increases, post-void residual urine volume and International Prostate Symptom Score (IPSS) also increase. Moreover in accordance with this finding, mean urinary flow rates and quality of life scores were statistically significantly decreased. In smoking addicts who have high mean package/year, post-void residual urine volume and IPSS levels were increased but proportionately maximum urinary flow rate and average urinary flow rate plus quality of life scores were found to be statistically significantly decreased. In patients with forced expiratory volume in first second:forced vital capacity (FEV1/ FVC) ratio less than 80%, mean urinary flow rates were found to be statistically significantly low. Also, we determined that in smoking addicts who have high mean package/year, erectile functions were statistically significantly impaired. Conclusion: We showed negative impacts of smoking addiction on LUTS, patient’s quality of life, and sexual functions.